Controlling Plasma-Functionalized Fillers for Enhanced Properties of PLA/ZnO Biocomposites: Effects of Excess l-Lactic Acid and Biomedical Implications - Cunha, Daniel A. L. V.; Marega, Felippe M.; Pinto, Leonardo A.; Backes, Eduardo H.; Steffen, Teresa T.; Klok, Larissa A.; Hammer, Peter [UNESP]; Pessan, Luiz A.; Becker, Daniela; Costa, Lidiane C. (American Chemical Society (ACS), 2025)
Plasma surface treatment of ceramic particles has emerged as a promising approach for developing biocomposites intended for use in tissue engineering applications. Introducing functional groups on particle surfaces promotes changes in material surface properties, enhancing adhesion, biocompatibility, and reactivity. It can also mitigate degradation during the processing of polymer matrices in composite materials. Therefore, carefully choosing the functionalizing agent responsible for generating the functional groups and selecting appropriate functionalization parameters are significant steps in the plasma surface treatment process. However, in a tissue engineering context, an excess of the functionalizing agent can be harmful, increasing cell toxicity and inhibiting the stimulation of cell growth, consequently delaying or even hindering tissue regeneration. This article examines how the functionalizing agent excess of l-lactic acid (LA) applied in the plasma surface treatment of the filler affects the thermal, rheological, biological, and wettability properties of poly(lactic acid) (PLA) and zinc oxide (ZnO) biocomposites. The investigation reveals that the surface treatment effectively mitigated the catalytic effects of ZnO on PLA degradation during melt processing, regardless of the excess functionalizing agent. There was minimal impact on the material’s rheological, thermal, and wettability characteristics, but the LA residue significantly influenced cell proliferation and the biological response. These findings show the importance of removing excess functionalizing agents to obtain biocomposites suitable for tissue engineering applications.
Keywords: biocomposites; excess functionalizing agent; material properties; plasma surface treatment; poly(lactic acid); washing; zinc oxide